Don't trust an(t)ybody - Pitfalls during investigation of candidate proteins for methylmercury transport at the placental interface. (July 2016) - Ellinger, Isabella; Chatuphonprasert, Waranya; Reiter, Martin; Voss, Agnes; Kemper, Jost; Straka, Elisabeth; Scheinast, Matthias; Zeisler, Harald; Salzer, Hans; Gundacker, Claudia
Abstract: While investigating placental mercury transport, we validated specificity of commercial antibodies against four candidate transporters (Large neutral amino acids transporter (LAT)1, LAT2, 4F2 cell-surface antigen heavy chain (4F2hc), and multidrug resistance-associated protein (MRP)2) by immunoblotting and small interfering RNA (siRNA)-mediated protein knockdown. An anti-4F2hc- and one anti-LAT1-antibody were specific. Another anti-LAT1-antibody reacted with LAT2. Two anti-LAT2-antibodies detected mainly albumin in placental lysates. A specific anti-MRP2-antibody hardly detected MRP2 in human placentas, contradicting published data. We recommend testing any unknown antibody by western blotting for 1/specificity for the protein of interest using e.g . siRNA knockdown and 2/cross-reactivity with albumin. Highlights: Specificity of commercial antibodies against LAT1, LAT2, 4F2hc, MRP2 was validated. We found an anti-LAT1 antibody to actually react with LAT2 instead of LAT1. Two anti-LAT2 antibodies detected mainly albumin in placental lysates. A specific antibody hardly detected MRP2 in human placentas, contradicting published data. Our findings underpin the need for rigorous validation of commercial antibodies.